Highly electrochemical stability of PEO-based polymer electrolytes for lithium-metal batteries - Nguyen Thi Hai Yen; Pham Minh Tuan; Pham Xuan Thao; Vu Quang Hung (Journal of Military Science and Technology, 2025)
Polyethylene oxide (PEO)-based polymer electrolytes, incorporating lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and succinonitrile, are highly promising for solid-state lithium-ion batteries due to their superior ionic conductivity and electrochemical stability. Electrochemical impedance spectroscopy (EIS), electrochemical stability window (ESW) are used in this study to assess the electrochemical performance of the electrolyte system. EIS exhibits ionic conductivities exceeding 10⁻⁴ S/cm at room temperature because of the plasticizing effect of succinonitrile, which reduces PEO crystallinity, and the enhanced ionic dissociation of LiTFSI. ESW measurements demonstrate a stability window surpassing 4.8 V, enabling compatibility with high-voltage cathodes. GPE-Li3 (MW = 600,000; mSN:mPEO = 0.2; mLi:mPEO = 0.2) exhibits the highest ionic conductivity (2.79x10-4 S/cm) and applied voltage up to 4.2 V, can be considered a promising gel polymer electrolyte configuration for lithium metal batteries.